Recent Advances on the Innate Immune Response to Coxiella burnetii - Sireci, Guido; Badami, Giusto Davide; Di Liberto, Diana; Blanda, Valeria; Grippi, Francesca; Di Paola, Laura; Guercio, Annalisa; de la Fuente, José; Torina, Alessandra (Frontiers in Cellular and Infection Microbiology, 2021)
Coxiella burnetii is an obligate intracellular bacterium Gram-negative and the causative agent of a worldwide zoonosis known as Q fever. The pathogen invades monocytes and macrophages, replicating within acidic phagolysosomes and evading host defences through different immune evasion strategies that are mainly associated with the structure of its lipopolysaccharide. The main transmission routes are aerosols and ingestion of fomites from infected animals. The innate immune system provides the first host defence against the microorganism and it is crucial to direct the infection towards a self-limiting respiratory disease or the chronic form. This review reports the advances in understanding the mechanisms of innate immunity acting during C. burnetii infection and the strategies that pathogen put in place to infect the host cells and to modify the expression of specific host cell genes in order to subvert cellular processes. The mechanisms through which different cell types with different genetic backgrounds are differently susceptible to C. burnetii intracellular growth are discussed. The subsets of cytokines induced following C. burnetii infection as well as the pathogen influence on an inflammasome-mediated response are also described. Finally, we discuss the use of animal experimental systems for studying the innate immune response against C. burnetii and discovering novel methods for prevention and treatment of disease in humans and livestock.